Identifikasi Learning Disability pada Anak Sekolah Dasar - Raharjo, Trubus; Kawuryan, Fajar; Ahyani, Latifah Nur (Lembaga Penelitian Universitas Muria Kudus, 2011)
This study aims to identify learning disability on elementary school children. Learning disorders faced by children who have learning disabilities are grouped in four criteria: dyslexia, disgrafia, dyscalculia, ADHD. Sample of this study were children of primary school class III and IV are considered to have problems with learning disabilities in the two districts at the county of Kudus who drawn at random. As for primary schools as the place to study as many as 10 elementary schools. Results of research conducted by observation, IQ tests and tests the ability to learn to identify learning disabilities in children of primary school of 209 children obtained the result that the child is having problems reading disabilities (dyslexia) as many as 43 children, children who experience an inability to write (disgrafia) as many as 20 children, children who experience disability numeracy (dyscalculia) as many as 13 children and none having attention disorder with hyperactivity, while based on the results of research on other samples experiencing slow learner disruptions as much as 97 children.